Peran Penyuluh (Da’i) Dalam Pembangunan Ekologi: Upaya Pengendalian Terhadap Kerusakan Lingkungan Hidup - Ari Rohmawati; Habib Ismail (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2018)
Environmental damage is a national issue at a time of global issues that become a very urgent problem that needs to be resolved given that the environment is part of the sustainability of human life in advance. Environmental degradation has an impact which is very crucial, namely drought, landslides, floods, coastal erosion, seawater intrusion, the uncertain climate change and others. The impact of the above will greatly affect the living conditions of the communities, either on the region's economic, social and cultural. Then the State has responsibility for rational and ethical responsibility to save the environment for sustainability of public life, including through the development of the role of the da'i as construction of extension officers in an attempt to damage control of the environment. This type of research is qualitative research using normative approaches. Its object is the extension officers of development of religion (Da'i) and ecological development. The methods used in this study is the study of librarianship.